Facile one-pot exfoliation and integration of 2D layered materials by dispersion in a photocurable polymer precursor - Gallardo, Carlos Alberto (2017)
Efficient exfoliation of graphene and related materials (GRM) and fast and inexpensive integration/assembly are crucial to fulfil their full potential. A high degree of exfoliation in organic media can be achieved with high boiling point liquids that usually leave residues after drying, which is a handicap for many applications. Here, the effective exfoliation and dispersion of GRM in a vinyl monomer, which is subsequently converted to a functional polymer by photopolymerization, is reported. Nanocomposite membranes and three-dimensional objects are produced by the photo-curing process and stereolithography 3D printing, respectively.